Theories of school counseling for the 21st century - Dollarhide, Colette T.; Lemberger-Truelove, Matthew E., 1976- (New York: Oxford University press, 2019)
"This unique book offers readers a compilation of contemporary and cutting-edge theories to inform the way school counselors practice the art and science of school counseling. Readers will gain tremendous insight into each theory, helping with selection of a favorite theory or contribute to theoretical flexibility for the school counseling practitioner"--
The context of professional school counseling : the need for theory / by Colette T. Dollarhide and Matthew E. Lemberger-Truelove -- General history and conceptual frameworks for school counseling / by Chris Slaten, Anya Woronzoff Verriden, and Thomas W. Baskin -- Organizational, institutional, and political challenges and responsibilities in professional school counseling / by Trish Hatch -- Person-centered school counseling / by Kimberly M. Jayne and Hayley L. Stulmaker -- Adlerian school counseling / by Erika R.N. Cameron, Kara P. Ieva, and Brianne France -- Cognitive-behavioral therapy in the schools / by Melissa Mariani and Brett Zyromski -- Counseling for results : reality therapy in action / by Robert E. Wubbolding -- School counseling from an existential perspective / by Brian Hutchinson and Tom Chavez -- Solution-focused school counseling / by John J. Murphy -- Strengths based school counseling (SBSC) 2.0 / by Patrick Akos, Clare Merlin-Knoblich, and Kevin Duquette -- Ecological school counseling / by H. George McMahon and E. C. M. Mason -- An advocating student-within-environment approach to school counseling / by Matthew E. Lemberger-Truelove and Hannah Bowers -- The discrimination model for school counseling supervision / by Melissa Luke and Kristopher M. Goodrich.
Includes bibliographical references and index.
Keywords: Educational counseling -- United States